A Structural Analysis of Nepal’s Maoist Movement and Gen-Z Struggles through a Large-Scale and Long-Run Perspective - Gyawali, Sindhu (NPRC Journal of Multidisciplinary Research, 2025)
The paper seeks to account for the Maoist Movement in Nepal and the recent Gen-Z activism through a macro-sociological perspective grounded in Pierson concept of long-run processes and Mishra’s analysis of large-scale structure of social change. It argues that both of these movements are repercussion against deep social inequality, weak accountability and persistent political instability. Using a comparative and historical approach, the study shows that while the Maoist movement ended the monarchy, it could not transform the underlying structural roots of inequality and paving the way for new forms of protest. The Gen-Z movement reflects a renewed search for justice, accountability, and social transformation in Nepal. From a Large scale and long run perspective, the Maoist movement was not a product of immediate or dramatic causes but must be understood with a broader historical and structural context. Nepal’s structural transformation thus remains an unfolding process, moving from one generation of insurgency to another form of civic reform.